Ultrasound experiments on acoustical activity in chiral mechanical metamaterials - Tobias Frenzel (Nature Portfolio, 2019)
Here, the authors report an effect analogous to optical activity in a 3D mechanical micro-lattice composed of chiral unit cells. They spatiotemporally resolve the motion of metamaterial beams at ultrasonic frequencies with nanometric precision and show up to 22° polarization rotation per unit cell.